STRATEGI KOMUNIKASI YANG DIGUNAKAN OLEH PELAJAR BAHASA INGGRIS DIKAWASAN KAMPUNG INGGRIS PARE DALAM KEGIATAN SPEAKING - Mariana, Lina (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2015)
Abstract: Language is a tool for both oral and written communication, technology, and culture. In fact, someone called a master in English if he/she has the communication skills that involve the ability of discourse: the ability of understanding and/or produce oral texts and/or written text that is embodied in the four language skills, namely listening, speaking, reading and writing. In verbal communication, there are many factors inhibiting one's communicative competence; linguistic problems include issues such as grammatical, lexical and phonological problems (Gan, 2013). The aim of this research is to find the empirical evidence about the communication strategies used by the English learners in Kampung Inggris pare especially in BTC program. In brief, the research questions of this research stated as follows: (1) What are the communication strategies used by the English learners in Kampung Inggris Pare on BTC program, and (2) what are the reasons of the English learners in Kampung Inggris Pare on BTC Program used communication strategies. This research is classified as descriptive qualitative using natural setting (naturally), although the qualitative approach in conducting the research, researcher also applied the descriptive method to describe the communication strategy adopted by English language learners. Subjects in this research were students who live in the Kampung Inggris Pare for one program, data collected from the implementation of communication strategies for the BTC program. Data drawn from three sources, namely: activities, informant, and documentation. In analyzing the data, the researcher used the Constant Comparative Method. The results of the research is shown that students in Kampung Inggris Pare at BTC Program applied communication strategies by doing word coinage, literal translation, code switching, and appeal for help, without the knowing. That was happed autonomous. Key Word: Communication Strategies, Kampung  Inggris Pare